Earnings Inequality and the Intersectionality of Gender and Ethnicity in Sub-Saharan Africa: The Case of Tanzanian Manufacturing - Elu, Juliet U; Loubert, Linda (American Economic Review, 2013)
This paper estimates quantile earnings functions with data from the 2004 Tanzanian Household Worker Survey to determine if ethnicity and gender–being female–matters per se and across the distribution of earnings. We find that in the Tanzanian manufacturing sector gender intersects with ethnicity to condition earnings and the return to schooling across the distribution of earnings. This suggests that in Sub-Saharan Africa–at least in Tanzania–labor market policies aimed at eradicating gender earnings inequality may not be effective if not accompanied by policies that also aim to eradicate ethnic inequality.